Recent Advances in the Synthesis of Biologically Active Compounds Containing Benzo[b]Furans as a Framework - M. Heravi, Majid; Zadsirjan, Vahideh (Current Organic Synthesis, 2016)
Benzofuran derivatives are the scaffold of many natural products, many of which are biologically active and/or found to have high potential as pharmacological agents. Therefore, benzofuran derivatives are expected to be invaluable moieties as far as biology and pharmacology are concerned. In this review, we try to highlight the recent advances in the synthetic approaches to a wide variety of its derivatives in particular those showing biological activity.
Keywords: Benzo[b]furan